GAMBARAN NILAI HEMATOKRIT DAN LAJU ENDAP DARAH PADA ANAK DENGAN INFEKSI VIRUS DENGUE DI MANADO - Kamuh, Sitti S. P.; Mongan, Arthur E.; Memah, Maya F. (Universitas Sam Ratulangi, 2015)
Abstract: Dengue is a major public health problem that can be found throughout the tropical and subtropical countries around the world. Spectrum of clinical manifestations of dengue virus infection varies greatly. In addition to clinical symptoms, the diagnosis of dengue virus infection need to be supported by blood tests such as hematocrit and erythrocyte sedimentation rate. This study aimed to determine the hematocrit value and erythrocyte sedimentation rate (ESR) in children with dengue virus infection in Manado. This study used a cross-sectional design and was conducted from Desember 2014 to January 2015 at GMIM Pancaran Kasih, Advent, and Robert Wolter Mongisidi hospitals in Manado. There were 37 patients that fulfilled the inclusion criteria, consisted of 17 males and 20 females. The results showed that of 37 patients, there were 36 with hematocrit within normal limits. Moreover, of 37 patients only 6 patients performed the ESR examination; only 1 child had a rapid ESR result (> 15mm/h). Conclusion: In this study, most of the pediatric patients with dengue virus infection in Manado had normal hematocrit. Of 6 patients who had performed ESR test, only 1 had rapid ESR.Keywords: dengue, hematocrit, erythrocyte sedimentation rateAbstrak: Dengue merupakan masalah kesehatan masyarakat yang utama dan dapat ditemui diseluruh daerah tropis dan subtropis di seluruh dunia. Spektrum manifestasi klinis infeksi virus dengue sangat bervariasi. Selain gejala klinis, diagnosis infeksi virus dengue perlu ditunjang hasil uji darah di laboratorium antara lain hematokrit dan laju endap darah (LED). Penelitian ini bertujuan untuk mengetahui nilai hematokrit dan LED pada anak dengan infeksi virus dengue di Manado. Penelitian ini menggunakan desain potong lintang, dilakukan pada bulan Desember 2014 sampai Januari 2015 di RSU GMIM Pancaran Kasih Manado, RS Advent Manado, dan RSAD Robert Wolter Mongisidi Teling17 anak laki-laki dan 20 anak perempuan. Hasil penelitian memperlihatkan 36 dari 37 pasien mempunyai hematokrit normal. Dasri 37 pasien, hanya 6 anak yang menjalani pemeriksaan LED; hanya 1 anak dengan LED cepat (> 15mm/jam). Simpulan: Pada studi ini, sebagian besar pasien anak dengan infeksi virus dengue di Manado mempunyai nilai hematokrit normal. Dari 6 pasien yang dilakukan pemeriksaan LED, 1 anak mempunyai hasil LED cepat.Kata kunci: dengue, hematrokrit, laju endap darah.